Answers

2016-01-24T10:35:10+05:30
You will get an equation n² - 15n + 44 = 0. n = 11 or n = 4.
0
  • qais
  • Content Quality
2016-01-24T10:56:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Easiest way is to write the terms in terms of a and d
6th term= a+ (6-1)d =a +5d
4th term = a +(4-1)d =a +3d
3rd term = a +(3-1)d =a +2d =15
A/q
(a +5d) = (a+3d)/2
⇒2(a +5d) = (a+3d)
⇒2a -a =3d -10d
⇒a =(-7d)
putting this in 3rd term.
 a +2d =15
⇒-7d +2d =15
⇒-5d =15
⇒d =(-3)
so, a = 21
now, sum of n terms = 66
(n/2)(2a +(n-1)d)= 66
⇒n(42 +(n-1)(-3)) =132
⇒45n -3n² =132
⇒n² -15n +44=0
⇒n² -11n -4n +44=0 
⇒n(n-11) -4(n-11)=0
⇒(n-11)(n-4) =0
either n=11 or n =4
after 4th term the sum of all terms will be zero.

0